Hammer mill offers affordable lime - Jere, Raphael (Technical Centre for Agricultural and Rural Cooperation, 2005)
As many farmers know, agricultural lime can be used to correct soil acidification, with the aluminium and manganese toxicity that goes with it, and the poor yields that result. Lime is an inexpensive mineral and in Zambia it is found throughout the countr